Beyond ideal models: non-idealities in TCAD simulations of dielectric-modulated FETs for label-free biosensing - Goswami, Rupam; Menon U, Vivek; Mitra, Suman Kumar; Deb, Deepjyoti; Das, Prachuryya Subash; Choudhury, Hirakjyoti; Gautam, Raja Vipul (Frontiers in Electronics, 2025)
Dielectric modulation in field-effect transistors (FETs) for label-free biosensing have been extensively explored to date, mostly due to the availability of semiconductor device technology computer-aided design (TCAD) tools. Of these works, many reports have revolved around TCAD simulations and focused on ideal or slightly deviated-from-ideal conditions, rather than on the inclusion of non-idealities to create actual biosensing test scenarios. This perspective presents a status of label-free dielectric-modulated biosensing in FETs. It highlights the five most important but rarely used or missing non-idealities in semiconductor TCAD tools, viz., multispecies representation, biomolecular kinematics, cavity profile, hybridization, and transient response. To better align TCAD frameworks with experimental studies, this article recommends adopting method-specific TCAD-integrated modeling (MSTIM) approaches.